Stolen Childhoods: Cape San Child Captives and the Raising of Colonial Subjects in the Nineteenth-Century Cape Colony (Historia, 2023)
Histories of indigenous child captives in settler-colonies remain marginal amid broader inquiries into colonial-era genocides of indigenous peoples. Yet, child transfers played an integral role in the demise of indigenous populations in numerous settler-colonies. Forced child removals occurred alongside the physical annihilation of parent societies and was often an important part of the erosion and eradication of hunter-gatherer peoples and identities. This article aims to set out an analysis of the integral role played by child abductions and transfers in the genocide of the Cape San during the early nineteenth century, with a particular focus on civilian initiative. In the Cape Colony, civilians initiated the practice of capturing and transferring San children to their invasive settler society. San children were considered malleable and better disposed to forced assimilation as labourers. Apprenticeship legislation was eventually introduced in the Cape Colony to regulate indigenous child transfers and to ensure that its worst abuses were minimised, although these ideals were seldom realised. Apprenticeship legislation attempted to catch up with existing practice set in motion by civilians and in effect, colonial authorities played an enabling role by legally legitimising it. The analysis also explores the narrative justifications for San child abduction and transfer employed by European-descended settlers, and contrasts these with contemporary evangelical-humanitarian discourses. Settlers and missionaries adopted different means to incorporate San children into settler society, while agreeing that incorporation was the desired end. Discursively, settlers and missionaries managed to frame their actions as being in the best interests of San children.
Keywords: San; Cape Colony; nineteenth century; childhood; genocide; forced labour; settler colonialism; child captives